Mountaineer Jamboree : Country Music in West Virginia - Tribe, Ivan M. (Book collections on Project MUSE., 1996)
Jamboree! To many country music fans the word conjures up memories of Saturday nights around the family radio listening to live broadcasts from that haven of hillbilly music, West Virginia. From 1926 through the 1950s, as Ivan Tribe shows in his lively history, country music radio programming made the Mountain State a mecca for country singers and instrumentalists from all over America. Wilma Lee and Stoney Cooper, Little Jimmy Dickens, Hawkshaw Hawkins, Red Sovine, Blaine Smith, Curly Ray Cline, Grandpa Jones, Cowboy Loye, Rex and Eleanor Parker, Lee Moore, Buddy Starcher, Doc and Chickie Will.